2020
DOI: 10.3390/app10176074
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Assessment Using Time–Frequency Analysis in Hypotensive and Non-Hypotensive Patients in Hemodialysis

Abstract: Intradialytic hypotension occurs in 10–30% of hemodialysis (HD) sessions. This phenomenon affects the cardiovascular system’s functions, which are reflected in the activity of the autonomic nervous system (ANS). To indirectly assess the ANS during HD, we analyzed the mean R–R intervals and the spectral power of heart rate variability (HRV) from 20 end-stage renal disease patients divided into hypotensive and non-hypotensive groups. The spectrotemporal analysis was accomplished using short-time Fourier transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Each method undergoes testing three times, and the comparison results are presented in Table 2 . And the average accuracy of the deep learning model mentioned in this paper can reach 99.33% higher than that of M1 (Time–Frequency Analysis) [ 34 ], M2 (ResNet-BiLSTM) [ 35 ], M3 (UNet-BiLSTM) [ 36 ], M4 (RNN) [ 31 ], M5 (LSTM) [ 24 ] and M6(GRU) [ 33 ], respectively, which reflects the advantages of the proposed model in the J-wave recognition task.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…Each method undergoes testing three times, and the comparison results are presented in Table 2 . And the average accuracy of the deep learning model mentioned in this paper can reach 99.33% higher than that of M1 (Time–Frequency Analysis) [ 34 ], M2 (ResNet-BiLSTM) [ 35 ], M3 (UNet-BiLSTM) [ 36 ], M4 (RNN) [ 31 ], M5 (LSTM) [ 24 ] and M6(GRU) [ 33 ], respectively, which reflects the advantages of the proposed model in the J-wave recognition task.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…Regarding the VLF band, this has been little studied because 5 min of HRV recording are not sufficient to capture it and estimate it with certainty [ 14 ]. Previous studies showed that the increase in intradialytic VLF is higher in patients who maintain a stable blood pressure compared to patients who develop intradialytic hypotension [ 15 , 19 ], suggesting the significant role of RAAS to preserve the hemodynamic stability.…”
Section: Discussionmentioning
confidence: 99%
“…The most common method to obtain HRV is through an electrocardiographic (ECG) recording, from which the time intervals between consecutive R waves are measured to form a time series called the HRV recording or R-R tachogram ( Figure 1 ). HRV assessment can be performed using time domain [ 10 ] or frequency domain analysis techniques [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Spectral analysis of HRV is accepted as an indirect method to assess interactions between the ANS and the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations